Evaluation Treatment Planning for Breast Cancer Based on Dose-Response Model - Aisyah, Siti; Hariyanto, Aditya Prayugo; Endarko, Endarko; Rubiyanto, Agus; Nasori, Nasori; Haekal, Mohammad; Nainggolan, Andreas (Jurnal ILMU DASAR, 2021)
The delivery of radiation therapy to patients requires prior planning made by medical physicists to achieve radiotherapy goals. Radiotherapy has a plan to eradicate the growth of cancer cells by giving high doses and minimizing the radiation dose to normal tissue. Evaluation of planning is generally done based on dosimetric parameters, such as minimum dose, maximum dose, and means dose obtained from the DVHs data. Based on the same DVHs, data were evaluate dinterms of biological effects to determine the highest possible toxicity in normal tissue after the tumor had been treated with radiation using the NTCP model. The evaluation was conducted by selecting three DICOM-RT data of post-mastectomy right breast cancer patients who had been prescribed a dose of 50 Gy obtained from the Hospital MRCCC Siloam Semanggi database. All data were processed using open-source software DICOManTX to get the DVH and isodose information. Matlab-based CERR software was used to calculate the NTCP model. The results show that the three patients' DVH and isodose treatment planning result in a homogeneous dose distribution result because the PTV area obtains adose limit of ≥ 95%. Moreover, normalt issue still gets adose below the tolerance limit based on the standard from RTOG 1005 and ICRU 83. Analysis of NTCP shows a complication probability below 1% for each organ, suggesting that any organ which has been irradiated has a low likelihood of complications. Therefore, it can be concluded that the treatment planning which has been made in the three patients using the IMRT technique has achieved the objectives of radiotherapy, which is to minimize toxicity to healthy organs. |Keywords: DVH, isodose, NTCP, radiotherapy.